Grammatical Errors in EFL Students' Writing - Ahmad Bowo Saputro (IAIN KENDARI, 2022)
This study sought to examine the frequency, and sources of writing errors committed by EFL students. To gather the information, 35 students were selected; the students were enrolled in a writing course in the second semester of academic year 2019–2020. They were asked to write three different topics of essays with 100 to 150 words in 40 minutes and requested to make reflection regarding the causes of errors according to their perception. The results of data analysis revealed that capitalization was the common mistake done by students followed by wrong word and punctuation. From students’ perception the causes of errors were 38% grammatical understanding, 21% vocabulary, 17% lack of idea, 13% in rush, 6% less practice and 5% less focus. The researcher believes that the causes of those errors were incomplete knowledge about basic writing and grammatical rules. According to the results, recommendations and any suggestions that are of importance to teachers and policymakers as well as to EFL learners are presented in detail.Keywords: EFL students; error analysis; grammatical error.